2020
DOI: 10.1177/0883073820940189
|View full text |Cite
|
Sign up to set email alerts
|

Care Delivery for Children With Epilepsy During the COVID-19 Pandemic: An International Survey of Clinicians

Abstract: Objective: To evaluate the effect of the COVID-19 pandemic on global access to care and practice patterns for children with epilepsy. Methods: We conducted a cross-sectional, online survey of pediatric neurologists across the world affiliated with the International Child Neurology Association, the Chinese Child Neurology Society, the Child Neurology Society, and the Pediatric Epilepsy Research Consortium. Results were analyzed in relation to regional burden of COVID-19 disease. Results: From April 10 to 24, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(95 citation statements)
references
References 27 publications
(35 reference statements)
4
86
1
4
Order By: Relevance
“…In fact, in a survey of 212 pediatric neurologists in 49 countries, more than 90% of physicians responding stated that in-person outpatient visits had decreased and use of telemedicine had increased. [ 31 ], The same study also found an approximately 90% decrease in EEG. As for the number of EEG tests, a survey of more than 200 Italian centers found a 75% reduction in the number of EEGs during the crisis compared to the pre-COVID-19 baseline, particularly in specific EEGs such as long-term monitoring/ambulatory EEG/polysomnography/video-EEG.…”
Section: Impact Of Covid-19 On Epilepsy Carementioning
confidence: 72%
“…In fact, in a survey of 212 pediatric neurologists in 49 countries, more than 90% of physicians responding stated that in-person outpatient visits had decreased and use of telemedicine had increased. [ 31 ], The same study also found an approximately 90% decrease in EEG. As for the number of EEG tests, a survey of more than 200 Italian centers found a 75% reduction in the number of EEGs during the crisis compared to the pre-COVID-19 baseline, particularly in specific EEGs such as long-term monitoring/ambulatory EEG/polysomnography/video-EEG.…”
Section: Impact Of Covid-19 On Epilepsy Carementioning
confidence: 72%
“…EEG-related papers (Table 4): While change in mental status has frequently been reported in patients with COVID-19 [26,27,55,60,65,66,70], and while there are many reports on clinical and subclinical seizures and status epilepticus in these patients [33-47, 63, 66], EEG studies have been significantly ignored and underused in these patients globally. Three studies showed that EEG services have been significantly disrupted by the pandemic of COVID-19 [18,19,57]. Three other studies showed that many of the patients with COVID-19 and encephalopathy/seizures had epileptiform discharges/seizures in their EEG [29,54,55].…”
Section: Resultsmentioning
confidence: 99%
“…Generally, care of patients changed dramatically during the lockdown period [9,11,12]. In regions with high COVID-19 burden, hospitals restructured and postponed, rescheduled, or even canceled outpatient visits by patients with chronic disorders, including epilepsy, both to respect physical distancing rules and to aid in resourcing for managing SARS-CoV-2 infections [1,13].…”
Section: Discussionmentioning
confidence: 99%